Unearthing Objects, Discovering Stories, and Retelling Lives. (2nd September 2017) - Prodromou, Amy-Katerini; Demetriou, Nicoletta
ABSTRACT: This introduction reflects on some of the topics raised in the special issue, especially how we tell—or retell—lives by discovering often long-hidden stories, and by unearthing objects thought to have been lost forever. The narrative presented here brings several stories together itself: that of the Doves type and its story of "lost and found"; that of the making of the special issue; and, even if briefly, that of Nicosia, the city that hosted the conference where several of this issue's contributions were shared for the first time.